Celebrating an Ecumenical Partnership. (2nd July 2016) - Gee, Ruth
Abstract : This study offers an example of 'standing theology', as distinguished from sitting or kneeling theology. The occasion was the celebration of the unfolding mission of a rural ecumenical partnership.